Preparation, Characterization, Theoretical and Biological Study of new Complexes with mannich base , 2chloro –N-5-(Piperidin -1-ylmethylthio)-1, 3, 4- Thiadiazol-2-yl)acetamide - Hasan, Noor A.; Baqer , Shaymaa R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
A new Mannich base ligand was prepared by reacting the 2-chloro.-N-(5-mercapto-1, 3, 4-thiadazol -2-yl) acetamide and Piperidine in the presence (formaldehyde) (L) ligand. A series of ligand complexes were prepared from (L) with the metal ion Co (II), Ni (II), Cu (II), Pd (II), Pt (IV), and Au (III). Various spectroscopic techniques such as C.H.N.S, FTIR, UV-VIS, , 1HNMR, 13CNMR, Magnetic moment, and molar conductivity successfully characterize the obtained compounds. The M: L ratio was determined using the molar ratio method in solution. All prepared compounds’ antibacterial and antifungal activity was studied against two types of bacteria and one type of fungi at a rate of 0.02M. The standard ΔH° f and ΔEb of the ligands and all the prepared complexes were calculated using Hyperchem 8.0.7 program, and the study proved that the complexes are more stable than the ligands. In addition, the vibrational frequencies of the ligand were calculated, and the theoretical error rate of the process was calculated.